Predictors of Health Insurance, Life Insurance, and Retirement Savings Among NYC’s Immigrant Taxi and For-Hire Vehicle Drivers - Gany, Francesca (J Community Health, 2020)
Taxi and for-hire vehicle (FHV) drivers are a predominantly immigrant population facing a range of occupational stressors, including lack of workplace benefits and increasing financial strain from tumultuous industry changes and now COVID-19’s devastating impact. Bilingual research staff surveyed 422 New York City taxi/FHV drivers using a stratified sampling approach in driver-frequented locations to examine drivers’ health and financial planning behaviors for the first time. Drivers lacked health insurance at double the NYC rate (20% vs. 10%). Life insurance and retirement savings rates were lower than U.S. averages (20% vs. 60%, 25% vs. 58%, respectively). Vehicle ownership was a significant predictor of health insurance, life insurance, and retirement savings. Compared to South Asian drivers, Sub-Saharan African drivers were significantly less likely to have health insurance and North African, and Middle Eastern drivers were significantly less likely to have retirement savings. Although most drivers indicated the importance of insurance and benefits, < 50% understood how to use them. Drivers felt primary care coverage to be most important followed by other health-related coverage, retirement benefits, and life insurance. Results reveal compelling addressable gaps in insurance and benefits coverage and the need to implement accessible financial literacy with navigation and advising services and programs.